Djibouti : Technical Assistance Report-Financial Soundness Indicators Mission. (IMF Staff Country Reports; Country Report ;, 2019)
In response to a request of the Central Bank of Djibouti (CBD), a mission from the International Monetary Fund's (IMF's) Statistics Department (STA) visited Djibouti during March 4-11, 2018, to provide technical assistance (TA) on the financial soundness indicators (FSIs). The main objectives of the mission were to: (1) ensure that the source data were adequate for the compilation of the FSIs; (2) assist the CBD in the compilation of the FSIs on the basis of the international standards set out in the IMF's Financial Soundness Indicators Compilation Guide (FSI Guide); (3) guide the staff of the CBD in the preparation of the FSI metadata in line with the IMF metadata forms; and (4) agree with the Banking Supervision Unit (BSU) on an action plan for the production of the FSIs and their regular reporting to STA.